2022
DOI: 10.4315/jfp-21-106
|View full text |Cite
|
Sign up to set email alerts
|

School Nutrition Professionals' Experiences with Food Safety and Special Diets in School Meals during the Initial COVID-19 Pandemic

Abstract: Federally funded school meals, such as the National School Lunch Program and School Breakfast Program, can help alleviate food insecurity. Meals served as part of these programs are required by law to be modified when medically necessary, such as food allergies and special diets. The coronavirus disease 2019 (COVID-19) pandemic caused many schools across the United States to close, but schools quickly modified meal-serving models. The purpose of this study was to understand the experiences of school nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Some of these challenges aligned with those described in prior research on summer meal programs, but were amplified by the pandemic: limited awareness of/dissatisfaction with the program, inconvenient times for families, lack of transportation, stigma, and limited options for religious conventions or dietary needs [37,38,41,46,49,53]. Pandemic-specific challenges included supply chain issues (i.e., being unable to receive the variety of foods obtained in the past), limited communication to families about how and where to access meals, and excessive waste [37][38][39]41,[45][46][47][49][50][51][52]54] Authors described how supply chain issues exacerbated family dissatisfaction-in one study, families reported stopping the use of the school meal programs because their kids refused to eat the food provided [53]. Parents in one study reported on a variety of ways that communication could have been more equitable (e.g., signage in multiple languages, more mail notifications for households without reliable Internet) [49].…”
Section: School Meal Programs Faced Both Familiar and Unfamiliar Chal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these challenges aligned with those described in prior research on summer meal programs, but were amplified by the pandemic: limited awareness of/dissatisfaction with the program, inconvenient times for families, lack of transportation, stigma, and limited options for religious conventions or dietary needs [37,38,41,46,49,53]. Pandemic-specific challenges included supply chain issues (i.e., being unable to receive the variety of foods obtained in the past), limited communication to families about how and where to access meals, and excessive waste [37][38][39]41,[45][46][47][49][50][51][52]54] Authors described how supply chain issues exacerbated family dissatisfaction-in one study, families reported stopping the use of the school meal programs because their kids refused to eat the food provided [53]. Parents in one study reported on a variety of ways that communication could have been more equitable (e.g., signage in multiple languages, more mail notifications for households without reliable Internet) [49].…”
Section: School Meal Programs Faced Both Familiar and Unfamiliar Chal...mentioning
confidence: 99%
“…Other operational challenges included staff burnout, staff illness, limited volunteer capacity, and staff feeling underappreciated [38,40,42,[45][46][47]50]; difficulty predicting participation numbers, particularly as a result of competition with other nearby food distribution programs and federal programs such as Pandemic EBT (a USDA food assistance financial benefit issued to families to support buying groceries during the COVID-19 pandemic) [38][39][40]46,47,50,52]; financial deficits resulting from increased operational costs and unpredictable participation numbers [40,41,47,50]; and food safety concerns, such as maintaining the cold chain with deliveries [43]. Food service directors also described challenges related to the USDA waivers, such as lack of adequate resources or knowledge to implement the waivers and a lack of communication from federal and state agencies [39,42,48,[50][51][52]54].…”
Section: School Meal Programs Faced Both Familiar and Unfamiliar Chal...mentioning
confidence: 99%